Pengaruh PjBL STEM terhadap Literasi Sains dan Problem Solving Siswa SMP - Afriana, Jaka (Jurnal Didaktika Pendidikan Dasar, 2022)
The Covid-19 pandemic requires immediate actions to break the spreading. This contextual problem needs to be discussed in science learning in schools so that the students can be the problem solvers. This study aims to determine the effect of PjBL STEM on students’ scientific literacy and problem-solving on the topic of environmentally friendly technology. The Matching-Only Posttest-Only Control Group design was used in the experimental class (N = 23) and the control class (N = 20). Experimental class learning utilized digital media with students’ final products in the form of hand sanitizers and digital science storytelling. The conclusion in PjBL STEM learning is that students’ scientific literacy in the aspect of competence in identifying scientific issues (Sig.=0,25 ˃ α = 0,05) and explaining scientific phenomena (Sig.= 0,13 ˃ α = 0,05), both the experimental class and the control class are not significantly different. Meanwhile, for the aspect of competence using scientific evidence (Sig. = 0,01 < α = 0,05), there was a significant difference between the experimental class and the control class. There is a significant (Sig. = 0,01 < α = 0,05) difference in the achievement of the average problem-solving scores of students in the experimental class and the control class.